Code Pocket: Development Of Interactive Online Learning Of STEM’s Subject - Zakaria, Nurul Azma; Zainal Abidin, Zaheera; Saharudin, Muhammad Shamil; Yusof, Robiah (Blue Eyes Intelligence Engineering & Sciences Publication (BEIESP), 2019)
Abstract: As to promote and develop STEM education in Malaysia, various approaches have been taken, including improving the curriculum of secondary school by enhancing the contents of the Technology subjects. In this paper, we are concentrating on the issues raised in learning and teaching the computer science subject specifically in supporting the students to understand the syllabus. We propose an interactive online learning application (Code Pocket) using Waterfall model to assist students in learning the subject and enables teachers to monitor the performance of the students. Code Pocket is a web-based application which acts as e-learning platform that consists of many modules such as notes, quiz and reporting. A dashboard menu panel is provided to enable easy navigation. This application provides alternative learning and teaching mechanisms by providing flexible learning environment that promotes online and mobile learning which can be accessed at anytime and anywhere. With interactive features, the learning experience will be better and interesting